Kontribusi Latihan Uphill Running Terhadap Peningkatan VO2MAX Tim Putra Sekolah Sepak Bola Pesawat FC Usia 13-15 Tahun - Mohamad Rizki Ali Ridho; Achmad Widodo (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Uphill running is a training method that utilizes natural conditions or the surrounding environment in the training process. The incline of the hill, the length of the track, and the training interval are the main keys that determine the contribution of this training. The initial aim of the research is to determine the contribution of uphill running training to increasing VO2max at the Pesawat FC soccer school, especially at the age of 13-15 years. The direction of this research will be presented in the form of a detailed explanation of valid research data obtained in the field. The sample for this research is 22 players aged 13-15 years from the Pesawat FC soccer school team. The research stage was carried out by grouping the sample into two control groups and an experimental group after carrying out an initial test, fairly using the ordinal pairing method. The results of the calculation analysis from the difference test from the collected data were that the difference between the pretest and posttest was quite large, namely that in the control group, it was only 4.08%. In the experimental group, it reached 15.69%. This means that the treatment of uphill running training in the experimental group had a greater effect on increasing VO2max. In the end, it was proven that there was a contribution from uphill running training to increasing VO2max for the FC Jombang Airplane soccer school team.